1998
DOI: 10.1097/00007890-199806150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Parvovirus Infection Potentiates Allogeneic Skin Graft Rejection and Induces Syngeneic Graft Rejection1

Abstract: These results suggest that MPV-1 infection of skin-grafted mice may disrupt normal mechanisms of peripheral tolerance and provide a unique model to study virus-induced autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…In a related study of BALB/c mice experimentally infected with MPV1a, infected mice had increased rejection of both allogeneic and syngeneic skin grafts, but the allogeneic-reactive T cells had decreased proliferative capacity. 85 No subsequent reports have corroborated these findings with any culture adapted or field strain of MPV. At this time, no long-term immunological effects have been shown for natural infection of mice with any field strain of MVM.…”
Section: Viral Agentsmentioning
confidence: 91%
See 1 more Smart Citation
“…In a related study of BALB/c mice experimentally infected with MPV1a, infected mice had increased rejection of both allogeneic and syngeneic skin grafts, but the allogeneic-reactive T cells had decreased proliferative capacity. 85 No subsequent reports have corroborated these findings with any culture adapted or field strain of MPV. At this time, no long-term immunological effects have been shown for natural infection of mice with any field strain of MVM.…”
Section: Viral Agentsmentioning
confidence: 91%
“…Two studies in the 1990s found altered immune function in mice experimentally infected with MPV1a, a culture-adapted strain discovered because of its effects on T-lymphocyte cultures. 85,84 In these studies, BALB/ c mice were inoculated with 10 6 TCID intraperitoneally and 10 5 TCID oronasally. Infected mice had accelerated rejection of tumor allografts but decreased killing by T cells.…”
Section: Viral Agentsmentioning
confidence: 99%
“…Anti-CD4 (GK1.5) and anti-CD8 (2.43) mAb in the form of ascites fluid were administered i.p. to B6-Igh6 KO donor mice, as described (29). Control mice were treated with an irrelevant mAb of the same isotype, D468.3.…”
Section: Figurementioning
confidence: 99%
“…For instance, BALB/c mice, infected by the B19 peptide, develop a strong anti-B19 parvovirus response and autoantibody activity against keratin, collagen II, cardiolipin, and single-stranded DNA. 49,50 However, the interaction between parvovirus B19 capsid protein and AT 1 receptor is far from understood. Epitope mimicry cannot be excluded and should be investigated further.…”
mentioning
confidence: 99%